2006
DOI: 10.1892/0891-6640(2006)20[13:dvofpa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Fasting Plasma Ammonia and Bile Acid Concentrations in the Identification of Portosystemic Shunting in Dogs

Abstract: Portosystemic shunting occurs frequently either as congenital anomalies of the portal vein (PVA) or as acquired shunting (AS) due to portal hypertension secondary to parenchymal liver disease or portal vein thrombosis. The 2 most commonly used screening tests for portosystemic shunting are bile acid and plasma ammonia concentrations. The purpose of this study was to compare the 12-hour fasting plasma ammonia (AMM) and bile acid concentration (BA) as tests for diagnosing portosystemic shunting. Medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
(30 reference statements)
3
26
0
1
Order By: Relevance
“…2,23,24 A recent study found baseline SBA concentrations to have a sensitivity of 92.2% for the detection of a congenital PSS and 81% for acquired shunting. 9 In our study, none of the dogs with tracheal collapse had increased baseline SBA and 2 of 11 dogs with a PSS were missed with only a fasting SBA measurement. These findings clearly indicate that baseline SBA concentrations are not consistently elevated in dogs with hepatic dysfunction and that the determination of stimulated SBA can give additional information when liver disease is suspected.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…2,23,24 A recent study found baseline SBA concentrations to have a sensitivity of 92.2% for the detection of a congenital PSS and 81% for acquired shunting. 9 In our study, none of the dogs with tracheal collapse had increased baseline SBA and 2 of 11 dogs with a PSS were missed with only a fasting SBA measurement. These findings clearly indicate that baseline SBA concentrations are not consistently elevated in dogs with hepatic dysfunction and that the determination of stimulated SBA can give additional information when liver disease is suspected.…”
Section: Discussionmentioning
confidence: 43%
“…Measurements of SBA in dogs with PSS resulted in a sensitivity of 64-100% in blood samples from fasted patients 3,4,9 and 100% in samples taken postprandially. [2][3][4] However, several factors can influence the postprandial (PP) values of SBA.…”
mentioning
confidence: 99%
“…[197][198][199] However, their sensitivity, particularly for early stage disease, is inadequate, which makes them poor screening tests for CH and thus should not be used as the basis for deciding to pursue hepatic biopsy. 189,192,200 However, TSBA concentrations are uniformly increased when portosystemic shunting is present, thus their sensitivity for detecting cirrhosis and the presence of APSS is high. 189 Dogs with cholestasis (ie, hyperbilirubinemia) associated with hepatic disease will always have increased TSBA.…”
Section: Function Testsmentioning
confidence: 99%
“…Hyperammonemia has similar sensitivity to detecting CH or cirrhosis and APSS as do TSBA, and it is somewhat more specific because it is not affected by cholestasis. 200 However, it is much more technically difficult to accurately measure blood ammonia concentrations. 197,[201][202][203][204] Although hyperammonemia infers the presence of HE, HE can develop in the absence of high blood ammonia concentrations.…”
Section: Function Testsmentioning
confidence: 99%
“…6 Hyperammonemia in dogs is mostly secondary to congenital portosystemic shunts (CPSS). [7][8][9] These CPSS are vascular anomalies that connect the portal vein to the systemic circulation, thereby bypassing the hepatic sinusoids. 10 As a result, blood flow from the portal vein through the liver parenchyma can be decreased by >95%, 11 carrying intestinal absorption products (eg, NH 3 ) directly into the systemic circulation.…”
mentioning
confidence: 99%